VALIDATION OF THE EIGHT NATURAL REMEDIES QUESTIONNAIRE – Q8RN – ADULT VERSION - Abdala, Gina Andrade; Meira, Maria Dyrce Dias; Isayama, Ricardo Noboro; Rodrigo, Gabriel Tagliari; Wataya, Roberto Sussumu; Tertuliano, Ivan Wallan (Journal of Interdisciplinary Lifestyle Studies, 2018)
The Eight Natural Remedies Questionnaire (Q8RN) comprises eight dimensions: nutrition, exercise, water, sunlight, temperance, pure air, rest, and trust in God. It is used to assess adherence to the healthy habits of the Adventist lifestyle. This article aims to analyze the attributes of validity and reliability of the Q8RN, adult version. Descriptive, methodological study, involving 504 participants of Health Fairs in Sao Paulo. Factorial Confirmatory Analysis (FCA) was performed in program R, with WLMSV estimation, polychoric type. There was evidence of validity of the Q8RN instrument, whose goodness of fit adjustments were: CFI = 0.965, Tucker-Lewis Index - TLI = 0.952 and Parsimony adjustment index RMSEA = 0.034. The eight dimensions were maintained, but the questions reduced from 25 to 22. Cronbach’s Alpha was 0.72, indicating internal reliability. The questionnaire reached adequate indexes, being considered a valid instrument to measure adherence to the eight natural remedies in adults.